2006
DOI: 10.1007/s10661-006-9295-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental properties on macrobenthos in the northwest Indian shelf

Abstract: Abstract. The paper deals with the standing stock of macrobenthic infauna and associated environmental factors influencing the benthic community in the shelf region of the northwest Indian coast. The data were collected onboard FORV Sagar Sampada during the winter monsoon (January-February, 2003) to understand the community structure and the factors influencing the benthic distribution. The environmental parameters, sediment characteristics and macrobenthic infauna were collected at 26 stations distributed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 25 publications
5
47
1
2
Order By: Relevance
“…The C : N ratios and δ 13 C values suggest that the organic carbon is of marine origin (Agnihotri et al, 2008). At a 30 m deep location (off Goa) on the inner shelf, Jayaraj et al (2007) observed benthic fauna such as polychaetes, crustaceans, mollusks and others, of which polychaetes comprised 83 %. At a 43 m deep site (off Bhatkal) on the inner shelf, Ingole et al (2010) also reported 43 taxa of benthic fauna such as polychaetes, crustaceans, oligochaetes, of which polychaetes comprised 85-95 %.…”
Section: Study Sitementioning
confidence: 93%
“…The C : N ratios and δ 13 C values suggest that the organic carbon is of marine origin (Agnihotri et al, 2008). At a 30 m deep location (off Goa) on the inner shelf, Jayaraj et al (2007) observed benthic fauna such as polychaetes, crustaceans, mollusks and others, of which polychaetes comprised 83 %. At a 43 m deep site (off Bhatkal) on the inner shelf, Ingole et al (2010) also reported 43 taxa of benthic fauna such as polychaetes, crustaceans, oligochaetes, of which polychaetes comprised 85-95 %.…”
Section: Study Sitementioning
confidence: 93%
“…Cluster 2 was differentiated into fine sediment texture with a high OM content; however, a low amount of DO and high sulphide with high OM content was observed at these stations. In this case, low species abundance and diversity was observed at stations 3 and 4, where high OM and sulphide adversely affect benthic fauna (Jayaraj et al 2007). This could also be evidenced from the An MDS plot based on the average abundance of molluscan fauna and environmental parameters revealed four distinct groups with a 32% similarity in the study area (Fig.…”
Section: Multivariate Analysesmentioning
confidence: 87%
“…Thus the low species richness of polycheates may be due to one or a combination of the above factors or the high level of pollution and eutrophication at these two sites. It could also be related to sediment properties and other environmental conditions prevailing in the area (Jayaraj et al, 2007).…”
Section: Discussionmentioning
confidence: 99%